Analysis of Business Development Strategy for Jember Party Equipment Rental Services Using the Business Model Canvas (BMC) Approach - Nur Muhlisoh Fauziyah; Arnis Budi Susanto; Sri Wahyu Lelly Hana Setyanti (Digital Innovation : International Journal of Management, 2025)
This study aims to describe the steps of business development strategies used in the Jember party equipment rental service business and describe, analyze the Business Model Canvas in the Jember party equipment rental service business. This study was conducted with a Business Model Canvas approach using a qualitative case study research type. Data collection using interviews and observations. The results of the study were obtained based on nine BMC elements consisting of customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structures summarized in one canvas showing that the Jember party equipment rental service business can carry out aggressive strategies. In addition, it also produces a new Business Model Canvas design as a result of improvements as a selected alternative strategy on channels , and customer relationships that can be used for future business development.